Treatment of Symptomatic Non-Parasitic Liver Cysts–Surgical Treatment Versus Alcohol Injection Therapy. Issue 4 (1990) - Furuta, Toshiya; Yoshida, Yasuhiro; Saku, Motonori; Honda, Hiroshi; Muranaka, Toru; Oshiumi, Yoshihiko; Kanematsu, Takashi; Sugimachi, Keizo
Abstract : Fourteen patients with benign symptomatic non-parasitic cysts of the liver were either surgically treated, had alcohol injected into the cysts, underwent deroofing of the cyst or in 5, a cystectomy was done. Alcohol was injected into 6 patients and there has been no recurrence for as long as 5 years and 8 months after the treatment. Liver dysfunction occurred in 3 patients given blood transfusion during the surgery and/or postoperative course, an elevated temperature (over 39℃) occurred in one patient. Adverse effects of alcohol injections were minor and transient. Based on our experience, the injection of alcohol is an effective treatment for benign symptomatic cyst of the liver. When a malignancy is suspected on imaging and/or cytologic studies, or when alcohol administration is ineffective, then surgery is indicated.